Improvement of Flame Retardancy of Polyurethane Foam Using DOPO-Immobilized Silica Aerogel - Zheng, Xin’guo; Dong, Quanxiao; Wang, Xi; Yu, Peiyun; Wang, Weimin; Zhang, Jinyong; Ren, Lin (Frontiers in Materials, 2021)
In this work, silica aerogel was modified by 9,10-dihydro-9-oxa-10-phosphaphenanthrene-1-oxide (DOPO). Then DOPO immobilized silica aerogel nanoparticles were used as flame retardant to prepare flame-retardant polyurethane foams. Microscale combustion calorimeter and cone calorimeter test were employed to evaluate the flame retardancy of polyurethane foams. It was found that both the heat release rate and the total heat release of the composites were reduced with the incorporation of DOPO immobilized silica aerogel. It is speculated that the DOPO-immobilized silica aerogel nanoparticles can inhibit the degradation of polyurethane and catalyze the formation of carbonaceous carbon on the surface.